2023
DOI: 10.1002/jemt.24333
|View full text |Cite
|
Sign up to set email alerts
|

Sonication and heat‐mediated synthesis, characterization and larvicidal activity of sericin‐based silver nanoparticles against dengue vector (Aedes aegypti)

Abstract: Fabrication, characterization and evaluation of the larvicidal potential of novel silk protein (sericin)‐based silver nanoparticles (Se‐AgNPs) were the prime motives of the designed study. Furthermore, investigation of the sericin as natural reducing or stabilizing agent was another objective behind this study. Se‐AgNPs were synthesized using sonication and heat. Fabricated Se‐AgNPs were characterized using particle size analyzer, UV spectrophotometry, FTIR and SEM which confirmed the fabrication of the Se‐AgN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Color shifting was observed during the synthesis of all three types of the NPs which was an indication of the successful fabrication of the NPs of different kinds as reported by multiple scientists in their respective studies (Tahir et al, 2020; Akhtar et al, 2023; Summer et al, 2023; Tahir et al, 2023; Summer et al, 2023; Subhani et al, 2023; Mumtaz et al, 2023; Akhtar et al, 2024; Mughal et al, 2024; Ali et al, 2023). The similarity of the present study with these previous findings suggested that the current study harbors authenticity and credibility for the synthesis of the NPs.…”
Section: Discussionsupporting
confidence: 57%
“…Color shifting was observed during the synthesis of all three types of the NPs which was an indication of the successful fabrication of the NPs of different kinds as reported by multiple scientists in their respective studies (Tahir et al, 2020; Akhtar et al, 2023; Summer et al, 2023; Tahir et al, 2023; Summer et al, 2023; Subhani et al, 2023; Mumtaz et al, 2023; Akhtar et al, 2024; Mughal et al, 2024; Ali et al, 2023). The similarity of the present study with these previous findings suggested that the current study harbors authenticity and credibility for the synthesis of the NPs.…”
Section: Discussionsupporting
confidence: 57%
“…[16] Conventionally, natural polymers are used as drug carriers as they are capable of incorporating antimicrobial agents. [17][18][19] However, the approach of natural polymers as antimicrobial agents is challenging due to their wide molecular weight variations and batch-to-batch variability. [20] The pharmacopeia now considers medicinal plants as a safe and comparatively biocompatible remedial source due to their promising results against numerous harmful microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan tends to degrade or lose its structural integrity under neutral pH conditions and becomes limiting in extreme pH conditions [16] . Conventionally, natural polymers are used as drug carriers as they are capable of incorporating antimicrobial agents [17–19] . However, the approach of natural polymers as antimicrobial agents is challenging due to their wide molecular weight variations and batch‐to‐batch variability [20]…”
Section: Introductionmentioning
confidence: 99%